Morphohistoarchitectonics of the reproductive system organs in cows with symptomatic infertility - Hryshchuk, H.; Huralska, S.; Kovalov, P.; Derkach, I. (Scientific Progress & Innovations, 2024)
In modern conditions, the problem of infertility among cattle remains relevant. The article reviews pathological and histological aspects related to infertility in cows. The aim of the study was to investigate the body status of infertile cows with symptomatic infertility based on morphological and histological examination of the internal genital organs. The ovaries, fallopian tubes and uterus of Ukrainian black-and-white cows were used for the study. The generally accepted methods of tissue fixation and preparation of sections for histological studies were used. It has been established that symptomatic infertility in cows is associated with hypotension and subinvolution of the uterus, inflammation of the fallopian tubes and ovaries, ovarian hypofunction, and hypoluteolysis. Based on the results obtained, it was proved that uterine hypotension is the main cause of inhibition of involution processes, leading to complications such as the cessation of lochia secretion and changes in the structure of the uterine horns. Morphometric studies of the fallopian tubes confirm the relationship between infertility and pathological changes in them. Histological examination of the genital organs of Ukrainian black-and-white cows with symptomatic infertility revealed the presence of hypertrophy of the folds and hyperplasia of the mucous membrane epithelial cells in the fallopian tubes. In some areas of the uterus, cells with cilia were found, and in the bends of the folds, the mucous membrane epithelium was absent, and connective tissue growth was observed in the glandular layer of the mucous membrane. Follicular atresia and folliculogenesis disorders in the ovaries were detected, which contributes to infertility. The general characterization of changes in ovarian structure indicates hypofunction and absence of follicles. Histologic changes, such as epithelial degeneration and desquamation, are key determinants of these pathologic conditions and may be important for the development of treatment and prevention strategies for this pathology. The obtained results contribute to a deeper understanding of morphohistological changes in the reproductive system of cows and their impact on reproductive functions, and can be the basis for developing effective strategies for the diagnosis and treatment of symptomatic infertility in cows.